Die Koninkryk van God - Grondplan van die Bybel - Heyns, Johan Adam (Verbum et ecclesia, 1994)
The Kingdom of God - Ground plan of the Bible The Bible does not only look like a book, in reality it requires to be read and understood as a book. But then not as a book written by a variety of authors with a great number of divergent and even contradicting stories, but as a book with a unique unity, in spite of its diversity of authors and perspectives. Through the authors God opens His heart for mankind and discloses His deepest intention with His creation.